2006
DOI: 10.1029/2005je002573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of geophysical investigations for detection of massive ground ice (pingo ice)

Abstract: [1] Six different geophysical investigations, (1) ground-penetrating radar, (2) DC resistivity sounding, (3) seismic refraction, (4) very low frequency (VHF) electromagnetic, (5) helicopter borne electromagnetic (HEM), and (6) transient electromagnetic (TEM) techniques, were employed to obtain information on the ice body properties of pingos near Fairbanks, Alaska. The surface nuclear magnetic resonance (NMR) data were also compared from similar sites near one of the study pingos. The geophysical investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…17a) and likely corresponds to a complex core of injection ice. These data are in accordance with resistivity values of pingo ice in Alaska (4500-18,000 Ω m) (Yoshikawa et al, 2006). In contrast, exceptionally low resistivity values (predominantly 10-400 Ω m, but up to 4000 Ω m) characterise the internal structure of Longyear Pingo (Fig.…”
Section: Resistivity Surveyssupporting
confidence: 76%
See 1 more Smart Citation
“…17a) and likely corresponds to a complex core of injection ice. These data are in accordance with resistivity values of pingo ice in Alaska (4500-18,000 Ω m) (Yoshikawa et al, 2006). In contrast, exceptionally low resistivity values (predominantly 10-400 Ω m, but up to 4000 Ω m) characterise the internal structure of Longyear Pingo (Fig.…”
Section: Resistivity Surveyssupporting
confidence: 76%
“…The use of capacitivecoupled resistivity systems (Timofeev et al, 1994;Hauck and Kneisel, 2006;de Pascale et al, 2008) or electromagnetic induction methods (e.g. Harada et al, 2000;Hauck et al, 2001;Bucki et al, 2004, Yoshikawa et al, 2006 have proved effective in overcoming problems of high contact resistance.…”
Section: Geophysical Propertiesmentioning
confidence: 99%
“…Mackay (1998) reports that the highest known pingo is Kadleroshilik Pingo 40 km southeast of Prudhoe Bay, Alaska, with 54 m above the surrounding lake plain. Limited examples of the internal structure of a pingo exist and are typically observed in rare cases of pingo collapse due to coastal, fluvial, or thermokarst erosion (Mackay, 1998), derived by mechanical drilling, or measured using geophysical techniques (Yoshikawa et al, 2006;Ross et al, 2005Ross et al, , 2007. Various morphological and structural characteristics of pingos and the dynamics of their formation and collapse are intensely discussed in the literature mentioned above and will therefore not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the potential of GPR for exploring permafrost environments, e.g., to estimate active-layer thickness (Arcone et al, 1998), to detect ground-ice bodies and ice layers (Yoshikawa et al, 2006;Brandt et al, 2007;De Pascale et al, 2008;Schwamborn et al, 2008), or to image specific periglacial morphologies (Doolittle et al, 1992;Moorman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%